Postcolonial Critical Pedagogy of English Language: Formulating Good Practices - Al-Mahmud, Abdullah (Journal of the Canadian Association for Curriculum Studies, 2020)
Initially due to colonial invasion, and later through globalization and neocolonial power relations, the English language has increased in its all-pervasive authority. The superior status of English over other languages is maintained in all sectors, including its pedagogy, at the structural level through gatekeeping policies, at the functional level through extending its scope, and the cultural level through the normalized attitudes and professional/social practices relating the language. To mitigate this situation and to advance the cause of linguistic decolonization and linguistic human rights, I intend to derive recommendable good practices for a Postcolonial Critical Pedagogy of English Language (PCPEL). The formulation of PCPEL is carried out by using the constructive grounded theory method under the methodological framework of generic benchmarking for an eclectic selection of quality statements suitable for multiple postcolonial settings. These quality aspects are accumulated from the relevant literature in a cross-matching and iterative or constant-comparative manner through coding, conceptualizing and categorizing. The outcome is a list of twenty quality standards under four quality categories for English language teaching (ELT)—ELT policy essues, ELT principles, ELT content, and ELT methods—which may be used as a quality framework to implement and assess ELT from a postcolonial critical perspective.